Optimizing the 7P Marketing Mix Strategy to Improve Local Supply Chain Competitiveness: Insights from Tatochis Corn Chips MSME - Nisa’, Siti Mufarohatin; Hasan , Fuad; Wijayanti, Dian Eswin (CV. SPDFHarmony, 2025)
Aim: Purpose: This study aims to explore the implementation of the 7P marketing mix strategy to improve the competitiveness of micro, small, and medium enterprises (MSMEs), with a focus on UD. Tajul Anwar, a local corn chip producer in Bangkalan, Indonesia.Method: A qualitative descriptive approach was used, involving observations, interviews, and questionnaires with key informants including the business owner, employees, resellers, and consumers. The data were analyzed through data reduction, display, and conclusion drawing, with triangulation applied to ensure data validity.Findings: The results reveal that product variety, improved packaging, accurate pricing, direct and indirect distribution, digital promotion, employee involvement, and enhanced service processes are crucial factors in strengthening market competitiveness. The use of the 7P framework allows for a comprehensive evaluation of marketing strategies and highlights the need for continuous adaptation in MSMEs.Significance: This research contributes practical insights for MSME practitioners by offering a structured marketing strategy that aligns with consumer expectations and business sustainability. The findings also provide a valuable reference for future studies aiming to develop competitive strategies for small businesses in local markets.